Analisis Frekuensi Alami Tanah di Daerah Rawan Longsor di Kecamatan Tomilito Menggunakan Metode Mikrotremor - Meilan Demulawa (Peneliti.net, 2022)
The research was carried out in Tomilito District, North Gorontalo Regency, which is an area prone to landslides. The purpose of this study is to determine the natural frequency of the soil. Data from the field or microtremor were analyzed using Geopsy software with HVSR (Horizontal to Vertical Spectral Ratio) which then obtained each natural frequency value of the soil. The conclusion of this study At points 1 and 4 the frequency values are in the range of 0.39 Hz -0.67 Hz included in the soil type IV classification including areas prone to landslides because in that area the soil is classified as soft soil formed from deltaic deposits, silt, delta sedimentation, silt, topsoil, humus, soft soil, points 2 and 3 are included in the soil type I classification with a natural frequency range of 18.31 Hz -19.93 Hz, while points 5 and 6 have a natural frequency of the soil is in the range of 3.32 Hz - 6.43 Hz included in the soil type II classification included in the soil type II and I classification, this area when a landslide occurs is still able to withstand the carrying load because the soil is included in hard soil.